2022
DOI: 10.3389/fncel.2021.787258
|View full text |Cite
|
Sign up to set email alerts
|

A Perspective on Nrf2 Signaling Pathway for Neuroinflammation: A Potential Therapeutic Target in Alzheimer's and Parkinson's Diseases

Abstract: Neuroinflammation plays a pivotal role in Alzheimer's disease (AD) and Parkinson's disease (PD), the leading causes of dementia. These neurological disorders are characterized by the accumulation of misfolded proteins such as amyloid-ß (Aß), tau protein and α-synuclein, contributing to mitochondrial fragmentation, oxidative stress, and neuroinflammation. Misfolded proteins activate microglia, which induces neuroinflammation, expression of pro-inflammatory cytokines and subsequently facilitates synaptic damage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 181 publications
(215 reference statements)
4
80
0
Order By: Relevance
“…This phenomenon is also observed in AD patients [35]. The correlation between low Nrf2 and AD can be explained due to Nrf2 playing a role in inflammation, oxidative stress, and influencing autophagy directly or indirectly [36][37][38]. Rojo [38,39].…”
Section: Nrf2 In Admentioning
confidence: 78%
“…This phenomenon is also observed in AD patients [35]. The correlation between low Nrf2 and AD can be explained due to Nrf2 playing a role in inflammation, oxidative stress, and influencing autophagy directly or indirectly [36][37][38]. Rojo [38,39].…”
Section: Nrf2 In Admentioning
confidence: 78%
“…Previous studies have reported different patterns of Nrf2 expression and its target antioxidant proteins in AD. Nrf2-ARE activation may occur in the early stage of disease and nuclear Nrf2 levels decrease in AD patients at a later stage ( 175 , 176 ). The demonstration that Nrf2 inducer SFN provides an improvement in cognitive function and amyloid pathology in PS1V97L‐Tg mice, has supported the importance of the Nrf2/ARE pathway in Alzheimer’s disease.…”
Section: Clinical Trials With Nrf2 Inducers Against Nlrp3 Inflammasom...mentioning
confidence: 99%
“…Nrf2 has been widely studied within the CNS [ 87 , 88 , 89 ]. Despite the different neurodegenerative diseases having diverse causes and consequences, oxidative stress is a common pathogenic mechanism in such disorders.…”
Section: Oncogenic Signaling Pathwaysmentioning
confidence: 99%
“…Loss of this function impairs the clearance of Aβ aggregates. p62 accumulates in the cytoplasm in absence of autophagy and interacts with the complex t Nrf2-Keap1 [ 89 , 97 ]. p62 releases Nrf2 from Keap1 and is translocated to the nucleus to induce the transcription of antioxidant enzymes and autophagy-related genes.…”
Section: Oncogenic Signaling Pathwaysmentioning
confidence: 99%